Inclusive secularism in Catalonia: comparing state and church schools - Vergés Gifra, Joan (Religion, state & society, 2020)
A number of recent studies highlight the attention the Catalan government has paid to religious matters since the year 2000. The efforts of Catalan institutions seem directed at fostering inclusive management of religious diversity. However, most of these studies focus on the steps followed at the ‘top’ level (legislative, governmental). In this article, in contrast, we adopt a ‘bottom-up’ perspective, enquiring to what extent efforts from the ‘top’ are present in the attitudes expressed by professionals in the city of Girona’s school sector. Rather paradoxically, we conclude that an attitude of inclusive secularism is less noticeable in state schools than in publicly subsidised Christian schools.